Peningkatan Hasil Belajar IPS Kenampakan Alam dan Sosial di Asia Tenggara dengan Metode Talking Stick - Sri Wiyanengsih (Perkumpulan Kualitama Edukatika Indonesia, 2022)
The formulation of the problem in this study is as follows: can the talking stick method improve student learning outcomes in social studies learning natural and social features in Southeast Asia in class VI SD Negeri Megonten 1 Kebonagung Semester 1 Academic Year 2018/2019?. This study aims to determine the increase in student learning outcomes in social studies learning natural and social features in Southeast Asia in class VI SD Negeri Megonten 1 Kebonagung Semester 1 for the 2018/2019 academic year through the talking stick method. This research was carried out in two cycles, each cycle designed four activities, namely the planning, implementation, observation, and reflection stages. The results showed that in the first cycle, the students' level of completeness only reached 64.7% (22 students) with a classical average of 71.2. In the second cycle there was an increase in student learning completeness to 94.1% (32 students) with a classical average of 81.5. So it can be concluded that through the application of the talking stick method, it can improve student learning outcomes in social studies learning material on natural and social appearances in Southeast Asia in class VI SD Negeri Megonten 1 Kebonagung Semester 1 of the 2018/2019 academic year.